2019
DOI: 10.1038/s41467-019-12651-2
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine modification of circNSUN2 facilitates cytoplasmic export and stabilizes HMGA2 to promote colorectal liver metastasis

Abstract: Circular RNAs (circRNAs) have been implicated in cancer progression through largely unknown mechanisms. Herein, we identify an N6-methyladenosine (m6A) modified circRNA, circNSUN2, frequently upregulated in tumor tissues and serum samples from colorectal carcinoma (CRC) patients with liver metastasis (LM) and predicts poorer patient survival. The upregulated expression of circNSUN2 promotes LM in PDX metastasis models in vivo and accelerates cancer cells invasion in vitro. Importantly, N6-methyladenosine modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
427
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 515 publications
(465 citation statements)
references
References 56 publications
10
427
0
Order By: Relevance
“…Moreover, circNSUN2 is a circular RNA that facilitates CRC cells metastasis and aggressiveness, and contains m 6 A methylation at the exon 5-exon 4 junction site [51]. On the one hand, YTHDC1 promoted circNSUN2 export from nucleus to cytoplasm.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, circNSUN2 is a circular RNA that facilitates CRC cells metastasis and aggressiveness, and contains m 6 A methylation at the exon 5-exon 4 junction site [51]. On the one hand, YTHDC1 promoted circNSUN2 export from nucleus to cytoplasm.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
“…On the one hand, YTHDC1 promoted circNSUN2 export from nucleus to cytoplasm. On the other hand, the KH3-4 di-domain of IGF2BP2 interacted with cir-cNSUN2 and then form a circNSUN2/IGF2BP2 complex to fortify the stability of HMGA2 that was a RNA inducing EMT and promoting CRC liver metastasis [51]. In addition, SOX2, an important gene to promote tumor initiation and metastasis, exhibited an elevated m 6 A level [52].…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al revealed that m6A recognized the binding of the protein YTHDF2 to the target molecule and recruited HRSP12 to mediate the cleavage of circRNA by the RNA endonuclease RNase P/MRP complex, suggesting critical significances to perceive circRNAs dynamic change [152]. Also, a new study from Chen et al demonstrated that the nuclear export of circNSUN2 is mediated by YTHDC1 in an m6A methylation-dependent manner [153]. All data highlights the significance of epigenetic alterations regulating the biogenesis and metabolism of circRNAs.…”
Section: Perspectivementioning
confidence: 99%
“…Furthermore, IGF2BP2 has recently been proven to mediate colorectal liver metastasis, testified both in vitro and in vivo with metastasis PDX models (72). Mechanistically, the m 6 A modification of circNSUN2 is recognized by YTHDC1, which accelerates the cytoplasmic export and further stabilizes HMGA2 mRNA by forming a circNSUN2/IGF2BP2/HMGA2 ternary complex in the cytoplasm.…”
Section: Igf2bpsmentioning
confidence: 99%